Static Characteristics and Unloading Effect of Deep Overburden Soil Ladder Arch Tunnel - Li MA; Yunhua LU; Qicai WANG; Xiaobo MA; Sheng LI; Kexun ZHANG (工程科学与技术)
Objective This study analyzes the static characteristics of trapezoidal arch openings and the unloading effect in deep overburden conditions to investigate the influence of the trapezoidal arch structure-fill interaction on surrounding soil pressure and unloading mechanisms. Additionally, it aims to clarify the advantages of trapezoidal arches over traditional rectangular arches.Methods This analysis combines indoor modeling tests and numerical simulations. In the experimental phase, organic glass plates serve as the test material. A numerical model and the specific thickness of the test material are deduced. Additionally, the preparation of a rubber granular soil mixture and its related compression and shear characteristic tests are conducted. In the numerical simulation phase, following verification with the indoor model test, the finite difference software FLAC3D and the discrete element software PFC2D are employed to establish the subway station model. Discrete elements primarily describe the fine contact between backfill particles, facilitating a better observation of the distribution of the contact force chain of the backfill around the openings. The static analysis of the deep overburden trapezoidal arch openings and their load unloading is also evaluated.Results and Discussions The study attributes the observed decrease in soil pressure to the gradual reduction of load shedding. The load reduction material enhanced the soil settlement at the top of the arch, creating a settlement difference within the soil column and forming a soil arch effect. This effect caused the soil pressure at the top of the arch to transfer to the sides, with the cross-section type exerting minimal influence on the settlement and distribution of the backfill above the opening. Before load reduction, the maximum axial force, the maximum positive bending moment, the minimum safety coefficient, and the maximum deformation of the lining in the trapezoidal arch roof slab opening all occurred at the central position of the roof slab. The maximum negative bending moment was observed at the interface between the straight roof slab of the trapezoidal arch and the sloping roof slab near the diaphragm wall. The maximum axial force, the maximum positive bending moment, and the maximum negative bending moment in the opening with trapezoidal arches were reduced by 17.5%, 34.1%, and 29.9%, respectively. The maximum deformations under working conditions T1, T2, J1, and J2 were 14.16, 9.50, 19.03, and 14.83 mm, respectively. Introducing a load-shedding layer did not alter the distribution of structural forces in deep overburden openings, but it significantly reduced the internal forces and deformation of metro stations, thereby enhancing the structural safety coefficient. The safety coefficients for various working conditions have been calculated according to the “Railway Tunnel Design Code”. The structural safety coefficients for trapezoidal arch caverns are in the following order: trapezoidal arch straight top plate < diaphragm wall < side wall < trapezoidal arch sloped top plate < bottom plate. For rectangular arch caverns, the order is rectangular arch top plate < diaphragm wall < side wall < bottom plate. The maximum and minimum safety factors for these two types of sections are found at the center of the top slab and the bottom slab of the unilateral cavern, respectively. Installing a load-shedding layer can increase the minimum safety coefficient of the trapezoidal arch and rectangular arch open caverns by 100.0% and 42.6%, respectively. Compared to trapezoidal arch roof subway stations, rectangular arch roof stations exhibit higher safety coefficients for the bottom plate and side wall but lower coefficients for the top plate, particularly at the center, which does not meet the specification requirements. The safety coefficients for trapezoidal arch roof subway stations increase significantly after installing a load-shedding layer, yielding a more pronounced effect. This study’s limitation lies in its sole focus on testing and numerical analysis to examine the internal force and deformation development in deep cover trapezoidal arch open holes under static force. However, it does not consider the substantial disturbances to the structure caused by backfill compaction during the open hole’s construction. Moreover, the study ignores the dynamic influences, especially seismic activities, and the development of solidification and settlement over time following the soil fill completion. These factors significantly affect the fill’s stress distribution and the structural force, posing a considerable impact on structural stability. Therefore, the dynamic effects, notably seismic actions, and the time-dependent consolidation and settlement after the completion require further investigation due to their substantial influence on the stress distribution of the fill and the structural stress, making them highly significant for research.Conclusions The results showed that in the absence of load shedding, the backfill settlement on both sides of the trapezoidal arch subway station exceeded the backfill settlement above the subway station, with the soil pressure on both sides of the subway station transferring to the top of the subway station. Furthermore, the soil pressure increased with the filling height, displaying a generally linear trend. During load shedding, the backfill settlement above the subway station was greater than on its sides, and the soil pressure gradually decreased with the increase of filling height.